Feasibility and Tolerance of Fingertip Peripheral Arterial Tonometry Measurements in School-Aged Children - Van De Maele, Karolien; Devlieger, Roland; Provyn, Steven; De Schepper, Jean; Gies, Inge (Frontiers in Pediatrics, 2021)
Background: Assessment of the endothelial function of the microvasculature by peripheral arterial tonometry (PAT) has gained increasing popularity in paediatrics. Discomfort or experienced pain during fingertip PAT has only been studied in adolescents and adults. Methods: In 142 children (aged 4 to 11 years old) a fingertip PAT with a commercial device (EndoPAT 2000®) as well as a calliper and ultrasound examination of peripheral skinfolds were performed as part of a cross-sectional cohort study. In 110 children, Faces Pain Scale (FPS-R) data was collected after PAT and skinfold measurements by calliper and ultrasound. Results: In 111 out of the 142 PAT measurements (78.2%), a reactive hyperaemia index (RHI) could be obtained. The most frequent error messages by the software was a “too noisy” and/or a “poor quality” signal. The success rate was higher in children aged older than 6 years (83.1% versus 44.4%; p<0.001). Median (range) FPS-R after PAT was 0 (range 0 to 6) but was significantly higher than the median pain experienced after calliper measurements of peripheral skinfolds (p< 0.001). No pain was experienced by 59 of the 110 children (54.1%). Conclusion: PAT testing is feasible in the great majority of school-aged children and the procedure is well-tolerated.